2017
DOI: 10.1007/s00244-016-0362-9
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated Biphenyl-Related Alterations of the Expression of Essential Genes in Harbour Seals (Phoca vitulina) from Coastal Sites in Canada and the United States

Abstract: As long-lived marine mammals found throughout the temperate coastal waters of the North Pacific and Atlantic Oceans, harbour seals (Phoca vitulina) have become an invaluable sentinel of food-web contamination. Their relatively high trophic position predisposes harbour seals to the accumulation of harmful levels of persistent organic pollutants (POPs). We obtained skin/blubber biopsy samples from live-captured young harbour seals from various sites in the northeastern Pacific (British Columbia, Canada, and Wash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 63 publications
2
2
0
Order By: Relevance
“…The tendency of upregulation of GR following the POP mixture exposure in killer whale cells is consistent with previous correlative studies on ringed seals and harbor seals showing positive correlation between GR expression and blubber levels of PCBs (Brown et al, 2014;Noël et al, 2017). GR plays a significant role in stress and immune responses, and alterations in the signaling pathway of glucocorticoid may interfere with these vital functions (Odermatt et al, 2006).…”
Section: Transcript Levels Of Genes In Cells Exposed To the Pop Mixturesupporting
confidence: 90%
See 1 more Smart Citation
“…The tendency of upregulation of GR following the POP mixture exposure in killer whale cells is consistent with previous correlative studies on ringed seals and harbor seals showing positive correlation between GR expression and blubber levels of PCBs (Brown et al, 2014;Noël et al, 2017). GR plays a significant role in stress and immune responses, and alterations in the signaling pathway of glucocorticoid may interfere with these vital functions (Odermatt et al, 2006).…”
Section: Transcript Levels Of Genes In Cells Exposed To the Pop Mixturesupporting
confidence: 90%
“…ERA and THRA expression showed a tendency of upregulation in relation to increased exposure of the POP mixture, which is consistent, at least for PCBs, with findings of a correlative study on killer whales (Buckman et al, 2011). Other field-based studies have also shown a positive correlation of THRA and ERA expression with PCB levels in harbor seal blubber (Noël et al, 2017;Tabuchi et al, 2006), and with ERA levels in ringed seal liver (Brown et al, 2014). Disruptions of these nuclear receptors involved in regulation of estrogen and thyroid hormones may cause disorder in regulation of estrogenic dependent processes, such as growth and reproduction (Cooke et al, 2001;Matthews and Zacharewski, 2000), or impact development, metabolism, or cell differentiation, respectively (Yen, 2001).…”
Section: Transcript Levels Of Genes In Cells Exposed To the Pop Mixturesupporting
confidence: 86%
“…An additional level of logistical complexity emerges with live captures of marine mammals to determine effects of contaminants. For example, live captures of harbor seals in the northeastern Pacific demonstrated correlations between PCB contamination levels and the expression of target genes in skin and blubber biopsies (Noël et al 2017), as well as disruptions of immune functions (Levin et al 2005; Mos et al 2006), thyroid hormones (Tabuchi et al 2006), and vitamin A (Mos et al 2007). Live captures of bottlenose dolphins with comprehensive health assessments have documented an association between PCB levels and anemia, hypothyroidism, and immune functions (Schwacke et al 2012) as well as an association between harmful algal bloom exposure and immune functions (Schwacke et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological research has indicated that higher maternal levels of POP exposures during pregnancy were associated with increased autism-related behaviors, poorer cognitive function, and reduced adaptive function [ 34 ]. POPs could affect the symptom domain of ASD by acting on SNP site of ESR1 gene [ 35 , 36 ]. Synapse appears to be a common susceptible target of POPs, altering dendrite and dendritic spine morphology, as well as synaptic function during sensitive developmental periods, leading to cognitive and behavioral dysfunction [ 37 ].…”
Section: Discussionmentioning
confidence: 99%